Environmentally friendly pervious concrete with recycled concrete aggregate - Lai, Ervin Jianwen (2011)
Living in a “concrete jungle” like Singapore, it is without a doubt that cement and its product, concrete, play a huge role in the life of a Singaporean. As such, one cannot neglect the environmental issues that arise as a result of the manufacturing of cement and the properties of its product- concrete.